Efektivitas Kebijakan Manajemen Bencana Dalam Mengurangi Dampak Sosial Dan Ekonomi - Nurhasna , Faicha; Saepudin , Eli Apud; Revita , Natasya; Cahya , Resma; Dewi, Salsabila Mustika (PENG: Jurnal Ekonomi dan Manajemen, 2025)
This research aims to increase the effectiveness of disaster management policies in reducing the social and economic impacts caused by natural disasters. With the increasing frequency and intensity of disasters, it is important to understand how implemented policies can minimize losses experienced by communities. The method used in this research includes qualitative and quantitative analysis of various policies that have been implemented in several disaster-prone areas. The research results show that disaster prevention policies based on community participation and the use of information technology have a significant positive impact in reducing social and economic losses. In addition, increasing local capacity through training and education has also proven effective in accelerating post-disaster recovery. These findings provide recommendations for policy makers to integrate more inclusive and adaptive approaches in disaster management to increase community resilience to the impacts of disasters.